Correlation of mandibular foramen to occlusal plane as a clinical guide for inferior alveolar nerve block in children: A digital panoramic radiographic study - Rashmi Hitesh Shukla; Amita Tiku (Contemporary Clinical Dentistry, 2018)
Aim: The study aimed to correlate the position of mandibular foramen with occlusal plane as a clinical guide for inferior alveolar nerve block (IANB) injection in children from 3 to 13 years of age. Materials and Methods: The study was carried out on 180 children visiting our department and required orthopantomogram as a routine diagnostic aid. Mandibular casts were obtained and radiographs were digitally analyzed to obtain linear and angular measurements. Statistical Analysis: The measurements were correlated with the position of mandibular foramen with Karl Pearson's correlation test. Results: The results of the study suggest that the needle for IANB should be placed below the occlusal plane in 3–4-year-old children (1.26 mm approximately), almost at the level of occlusal plane in 5–7 years (0.33 mm), above the occlusal plane in 7–9 years (1.54 mm), 9–12 years (1.64 mm), 11–12 years (1.98 mm), and 12–13 years (2.9 mm), respectively. The distance of the mandibular foramen from anterior border of mandible was greater than that from posterior border. The gonial angle values decrease with increasing age. Conclusion: The bony landmarks within the jaws keep changing their relative positions along with the skeletal growth. It is therefore necessary to modify the placement of needle during local anesthesia techniques with advancing age.